2020
DOI: 10.3168/jds.2019-16787
|View full text |Cite
|
Sign up to set email alerts
|

Studying stirred yogurt microstructure using optical microscopy: How smoothing temperature and storage time affect microgel size related to syneresis

Abstract: A grainy texture and high syneresis are 2 defects in low-fat stirred yogurt that are often disliked by consumers. In this study, a rheometer controlling the shear rate and temperature was used to simulate the smoothing step of yogurt manufacture. Identical formulations containing whey protein isolate or whey protein concentrate were compared. After the yogurt milk underwent heat treatment, inoculation, and fermentation at 42°C, the yogurt was smoothed at 42°C (Y42) or 20°C (Y20) or during a cooling ramp from 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 39 publications
(88 reference statements)
2
49
0
1
Order By: Relevance
“…La viscosidad podría aumentar durante el enfriamiento a menor temperatura antes del suavizado y esto puede conducir a una mayor ruptura de la red de proteínas. Gilbert et al (2020) obtuvo los mismos resultados al suavizar el yogur con un reómetro 42 °C dando un valor de sinéresis más alto que el yogur suavizado a 20 °C. Diversos autores coinciden en que el batido a 20 °C es ideal para obtener yogur de alta calidad, que se supone que incluye valores de sinéresis más bajos (Robinson, Lucey, & Tamime, 2007), debido a que si se suaviza el yogur a una temperatura cercana a la temperatura de incubación dañaría la estructura de la red de proteínas haciéndola más frágil (Lucey, 2004).…”
Section: Batido O Suavizadounclassified
“…La viscosidad podría aumentar durante el enfriamiento a menor temperatura antes del suavizado y esto puede conducir a una mayor ruptura de la red de proteínas. Gilbert et al (2020) obtuvo los mismos resultados al suavizar el yogur con un reómetro 42 °C dando un valor de sinéresis más alto que el yogur suavizado a 20 °C. Diversos autores coinciden en que el batido a 20 °C es ideal para obtener yogur de alta calidad, que se supone que incluye valores de sinéresis más bajos (Robinson, Lucey, & Tamime, 2007), debido a que si se suaviza el yogur a una temperatura cercana a la temperatura de incubación dañaría la estructura de la red de proteínas haciéndola más frágil (Lucey, 2004).…”
Section: Batido O Suavizadounclassified
“…The Rvis was calculated using a protocol described by Küçükçetin et al (2012). The microscopic image of the ayran samples was taken at 10x magnifications by a fluorescent microscope (MCX300, MICROS Produktions und Handels GmbH, Veit/Glan, Austria) (Figure 2 a-h) (Gilbert et al, 2020).…”
Section: Graininess and Visual Roughnessmentioning
confidence: 99%
“…During the post-fermentation process, stirring and smoothing steps take place in a continuous circuit, where the gel undergoes different levels of structure modification through pipes, pump, cooling devices, and finally smoothing nozzle (Chandan and O'Rell, 2013;Mokoonlall et al, 2016). These processing treatments induce mechanical shearing that creates a new microstructure for stirred yogurt (Mokoonlall et al, 2016;Gilbert et al, 2020b). Microscopic observations (scale between 10 µm and 250 µm, depending on the study) have revealed highly disrupted and reorganized protein network with intact microfragments (microgels) from the initial set gel (van Marle, 1998;Laiho et al, 2017;Gilbert et al, 2020b;Gregersen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These processing treatments induce mechanical shearing that creates a new microstructure for stirred yogurt (Mokoonlall et al, 2016;Gilbert et al, 2020b). Microscopic observations (scale between 10 µm and 250 µm, depending on the study) have revealed highly disrupted and reorganized protein network with intact microfragments (microgels) from the initial set gel (van Marle, 1998;Laiho et al, 2017;Gilbert et al, 2020b;Gregersen et al, 2021). Microgels can be defined as dense protein aggregates; their sizes and rigidity have been identified as important parameters for understanding the perceived granularity of stirred yogurt (Cayot et al, 2008;Laiho et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation